O envelhecimento e a homossexualidade masculina - Cunha, Luciana de Almeida da (2014)
Discussions on human rights of elderly homosexuals are very relevant in the current context. Such relevance is due, among other things, the progressive increase of the aging population and life expectancy. Because they are inserted into a doubly discriminated segment, homosexuals elderly become targets of prejudice in the labeling of derogatory stereotypes. In this perspective, the study - descriptive, with a qualitative approach - aims to evaluate the impact of homo-affective sexual orientation in the life trajectory of elderly men. Were interviewed four homosexuals elderly individuals, aged between 60 and 65 years, and the data collected were analyzed using the technique of content analysis of Bardin. The results were structured around four categories: remembering the discovery of sexual orientation; about sexual orientation and positioning of the family; be assumed as gay: observation of social response; in the living and aging process, "no matter be hetero or homo," everyone follows his course. The narratives of elderly homosexuals reveal social prejudice faced in different contexts. Their life histories, in daily life, resemble those of other people, once, regardless of their sexual orientation, they have studied, worked and constituted families. Their perceptions about living and aging in this condition, with the exception of episodes of prejudice shown by homophobic people, had positive repercussions in their life trajectory